A presença do trágico em Memórias de Lázaro e Corpo vivo: um estudo da narrativa de Adonias Filho - Silva, Wanessa Guimarães da (2011)
Are discussed in this dissertation as the tragic events are present in the narrative of Adonias Filho, namely: Memórias de Lázaro (1952) and Corpo Vivo (1962). This is the reading and analysis of how tragic it is worked by the author in the works mentioned above, leading us to the depths of hell and the human soul, producing feelings of purging and cathartic relief for pain and suffering in human misery. Hopelessness, incest, patricide and filicide (crimes against his own blood), ironic fate, scary violence and crime, etc.., Are present on the lines of narrative Adonias Filho amalgamates the influence of classical themes, as marked in the history of literature universal. In Memórias de Lázaro and Corpo Vivo, works of great aesthetic impact the holding of language and images, narrated dramas pervade a higher plane of human aspirations in a way of being in a world of pain and disappointment. Here we place the work of Adonias Filho a broader reflection about the actions of man in the world, thinking that is present in the composition of the desperate inner universe of the characters fall into the abyss of their own souls.